When digital natives enter the electorate: Political social media use among first-time voters and its effects on campaign participation. Issue 2 (3rd April 2019) - Ohme, Jakob
ABSTRACT: In this study, we explore the media exposure of digital native first-time voters and test for its mobilizing potential for their campaign participation. We compare first-time voters' and experienced voters' exposure to political information on social network sites, non-social online media and offline media . Using a unique research design that involves a smartphone-based diary study, we assess voters' (n = 1108) media exposure every other day of the Danish parliamentary election campaign in 2015. We distinguish between different content types that first-time voters receive on social media and test for variation in the mobilizing potential of these content types. Findings show that social media platforms play a superior role in the media diet of digital native voters and can foster campaign participation. First-time voters are more exposed to direct communication from political actors than experienced voters while content from news media on social media plays an equal role in both groups' media diet. Results suggest that a digital media environment potentially socializes young voters into polarized information environments that nevertheless may increase their involvement in an upcoming election.